Ekologija teksta in ruska kultura 20. stoletja - Javornik, Miha (Primerjalna književnost, 2007)
A theoretically planned discussion of 20th-century Russian culture must be understood as a conceptual and methodological starting point that makes it possible to reveal the dynamics of its development. The avant-garde metaphor of the zero or circle as an ideal signifying everything or nothing is placed at the forefront. Russian culture uses various means to purify its expression to express this ideal. On the other hand, its neurotic aspiration for the pure, natural, and primary continually brings it back to the sensation of the Nothing.
Keywords: ruska kultura; Russian literature; ruska književnost; 20.st.; avantgarda